EXPERIENCE OF WORK OF THE ANTI-CORONAVIRUS CENTER IN "GRAND MEDICA LLC" - Вероника Владимировна Манжос; Вячеслав Игоревич Виндюрин; Андрей Александрович Косовских; Андрей Игоревич Баранов (Медицина в Кузбассе, 2021)
The article analyzes the experience of the anticovidar center in the conditions of the private medical center "Grand Medica". In November, December 2020, 119 patients with a new coronavirus infection received treatment, including 49 (41.2 %) men and 70 (58.8 %) women. The average age of patients was 61.2 ± 13.1 years, while in men it was 58.6 ± 13.8 years, in women – 63.0 ± 12.3 years. The difference in age between men and women was statistically significant, p = 0.040. The duration of treatment of patients before hospitalization was 12.0 ± 4.9 days and the severity of the course of the disease was not associated with this indicator. The mortality rate was 3.4 % and it is associated with the death of 4 patients aged 59, 72, 73 and 81, respectively. There were 84 (70.6 %) patients who received all treatment in a therapeutic department; patients who were initially treated in the therapy department, but due to worsening respiratory failure were transferred to the intensive care unit – 10 (8.4 %) people; patients admitted directly to the intensive care unit (ICU) – 25 (21.0 %) people. Significant increases in C-reactive protein, D-dimer levels, and fibrinogen levels were predictively significant factors suggesting the possibility of deterioration.